Outcome evaluation of U.S. Department of State support for the Global Methane Initiative - Burger, Nicholas E. (Technical report (Rand Corporation), 2013)
Methane is a short-lived greenhouse gas that is released during the production and transport of coal, natural gas, and oil; the raising of livestock and other agricultural practices; and the decay of organic waste in municipal solid waste landfills and some wastewater treatment systems. Although it is short-lived, methane has more than 20 times the atmospheric warming effect of carbon dioxide. However, it is a primary component of natural gas, so efforts to reduce methane emissions can take advantage of technologies that capture and reuse the gas as a fuel, potentially bringing about cost-effective reductions in emissions. The Global Methane Initiative (GMI) is a voluntary international partnership that promotes methane recovery and reuse activities in developing and transition economies. Program partners and funders include national governments, private-sector firms, development banks, and nongovernmental organizations. As a founding member of the partnership, the U.S. government contributes funding and other types of support to GMI primarily through the U.S. Department of State (specifically, its Bureau of Oceans and International Environmental and Scientific Affairs and its Office of Global Change) and the U.S. Environmental Protection Agency. To help gauge the effects and value added of its support for the program, the Department of State requested an evaluation of GMI's activities and outcomes relative to its contributions in fiscal years 2006-2010. The evaluation employed a mixed-methods approach that combined quantitative and qualitative information to document program resources and activities and to illustrate program outcomes, including information from in-country site visits. The report also presents some recommendations for how data collection could be improved to answer more sophisticated questions in the future about the effectiveness of GMI and the value added by the department's contributions.